Physicochemical dynamics water in a tropical floodplain - Néstor Aguirre R.; Yimmy Montoya M. (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
We studied the physicochemical variables change in seven water swamps and seven streams outside the floodplain area Ayapel in nine samples during the period 2006-2009. The average value of electrical conductivity in the swamp is three times less than the value of the swamps of the region. 100 μS/cm can be considered as discriminating among swamps with lower values, and streams with higher values. There was no relationship between transparency and the concentration of photosynthetic pigments, which could be considered as an indicator a lower level trophic system. Temporary level all evaluated forms of nutrients present differences which indicates the importance of the effect of the pulse of flooding through the hydrological cycle. With the decline of the column of water in times of drought, there was an increase in the concentrations of nitrogen, which are favored by the resuspended material from the bottom of the swamp. Phosphorus concentration is most sensitive to spatial variation, this nutrient cycle is very associated with the sediments and the composition of the soil of each basin. We found that for the same phase in successive cycles of the pulse, there are differences in the system dynamics so that when the hydrologic sampling is performed is the main factor in the behavior of the physicochemical conditions of the system.